Development and Evaluation of an Augmented Reality Chiller System Simulator for TVET Teaching - Abdul Jalil, Muhammad Zuhairi; Razali, Nizamuddin; Abdul Rahman, Khairul Anuar; Rahim, Mohd Bekri; Abd Samad, Noorazman (Journal of Technical Education and Training, 2024)
This study investigates the potential of Augmented Reality (AR) technology to enhance teaching quality in courses on Water Cooled Chillers and Air-Cooled Chillers. It addresses the critical need for more interactive and engaging learning experiences, particularly for students in skills-based institutions who often exhibit a preference for visual and kinesthetic learning styles. Highlighting the importance of diversifying teaching methods, this research aims to improve student engagement and deepen their understanding of complex subject matter. Utilizing the ADDIE design model, the study develops an AR simulator and assesses its effectiveness through a questionnaire distributed to students from three vocational colleges. A descriptive analysis method was employed to evaluate the data, with the research instrument demonstrating a high reliability value (α = 0.890). The findings reveal significant levels of perceived usefulness (M = 4.34), ease of use (M = 4.36), and positive attitudes (M = 4.25) towards the AR simulator. Consequently, the study concludes that AR technology is highly accepted among vocational college students, recommending the broader incorporation of AR technology in vocational education to enhance the efficacy of the teaching and learning process.